; Agricultural restructuring in Turkmenistan - Stanislav Aganov; Yolbars Kepbanov; Gurbanmyrat Ovezmuradov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
. , . , . , . 1992-2013 . 25 %, , , . – – This report presents the main issues of land reform and agricultural restructuring in Turkmenistan. The first part of the report focuses on the progress of agrarian reform by providing a chronicle of the main agricultural policies, before presenting an overview of the organizational structure of input and resource supply in agriculture. The main body describes the changes in cropping pattern, and the development of different types of agricultural producers by highlighting their contribution to sectoral development and food security. The study shows that land reforms and agricultural restructuring in Turkmenistan were carried out under the central role of the state. As a result of the progress of agricultural reforms, the total sown area in Turkmenistan expanded by 25 %. However, peasant associations based on the land lease system, remain the main farm category in agricultural production and are assigned the primary task of fulfilling the state order in strategic crops.
urn:nbn:de:gbv:3:2-69679
Keywords: P41; P47; Q15; Q18; 330; food policy; farm restructuring; agricultural diversification